Food insecurity among disabled adults. (13th May 2022) - Hadfield-Spoor, Mia; Avendano, Mauricio; Loopstra, Rachel
Abstract: Background: The relationship between disability and food insecurity is under-researched. Risk of food insecurity may vary by type and number of disabilities. We examine the hypotheses that (i) a higher number of disabilities increases risk of food insecurity and (ii) associations of physical disabilities, mental/cognitive disabilities or a combination of both types with food insecurity may differ in strength. Methods: Data came from the fifth wave of the UK's Food Standards Agency's Food and You survey (2018), which contains detailed information on disability and household food insecurity. We used logistic and multinomial logistic regression to model the number and type of disabilities as predictors for food insecurity outcomes, controlling for socio-demographic factors. Results: Both type and number of disabilities predicted food insecurity. Every additional disability was associated with higher odds of food insecurity [odds ratio (OR): 1.60, 95% confidence interval (CI): 1.40–1.83]. Among people with a disability, every additional disability was associated with 19% higher odds of food insecurity (OR: 1.19, 95% CI: 1.05–1.34). People with both physical and mental/cognitive disabilities had increased odds of severe food insecurity (OR: 8.97, 95% CI: 3.54–22.7). Conclusion: Number and type of disabilities are associated with higher risk of food insecurity. A combination of physical and mental/cognitive disabilities, as well as having multiple disabilities are each independently associated with higher risk of food insecurity. Policy-makers may thus consider using targeted and tailored policies to reduce barriers to social and financial inclusion of disabled people to reduce food insecurity.